A fuzzy logic model for students' scholarship selection / Nor Hashimah Sulaiman and Daud Mohamad - Sulaiman, Nor Hashimah; Mohamad, Daud (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2006)
Fuzzy logic has been successfully applied in many fields such as in engineering, computer science and management sciences. One of its useful applications is in decision-making where, in "real world" problems, factors involved are normally vague. Formulation of the problems using common approaches would be difficult due to the situation that have an inherent lack of precision. In this paper a fuzzy logic model has been developed for the selection process of students applying for scholarship. The selection is based on certain criteria determined by the sponsor. An example is given at the end of the paper to illustrate the model. The MATLAB fuzzy logic tool box is used to calculate the output.